Growth and determinants at two years of age in a South African birth cohort - Itzikowitz, Raphaela (Department of Paediatrics and Child Health, 2025)
Aim: Early childhood is a critical period for optimal growth but there are limited data from low- and middle-income countries (LMICs) on the determinants of growth during this time. This study aimed to investigate growth and its determinants in children at 2 years of age in a South African birth cohort in a resource-limited region. Methods: Mother-child pairs enrolled in a South African birth cohort, the Drakenstein Child Health Study (DCHS), were followed from birth to two years. Comprehensive socio-demographic and psychosocial data collected during the antenatal period and nutritional information, intercurrent illness and immunisation data collected longitudinally in the first 2 years was used. Anthropometric data, measured at 2 years, were analysed as z-scores adjusted for child age, sex, and prematurity, and used to classify undernutrition (wasting, underweight for age and or stunting), overweight for age or obesity. Logistic regression was done to identify predictors of undernutrition, overweight or obesity at 2 years. Results: Anthropometric data from 897 children (51% male; 22% HIV-exposed, uninfected) were included. 69 (8%) were underweight, 20 (2%) were wasted and stunting occurred in 167 (19%) children; 116 children were overweight (13%), and 42 were (5%) obese. Overall, 351 (39%) had some form of growth impairment. Higher birth weight, or length, higher maternal height or better maternal education were associated with lower odds of undernutrition or stunting at 2 years. Male sex, antenatal maternal smoking or prematurity were associated with increased odd of undernutrition or stunting. Higher birth weight was associated with increased odds of being overweight for age. Better maternal education was associated with increased odds of obesity, but antenatal smoke exposure reduced the risk. Conclusion: There is a substantial burden of malnutrition in South African children during early childhood encompassing both undernutrition and obesity. Stunting, indicative of chronic growth impairment, is most prevalent. Antenatal risk factors are important predictors of poor growth outcomes. Strengthened strategies to improve childhood nutrition and address modifiable factors in the antenatal and early childhood periods are needed.